Non-covalent functionalization of reduced graphene oxide using sulfanilic acid azocromotrop and its application as a supercapacitor electrode material - Jana, Milan; Saha, Sanjit; Khanra, Partha; Samanta, Pranab; Koo, Hyeyoung; Murmu, Naresh Chandra; Kuila, Tapas (ROYAL SOC CHEMISTRY, 2015)
Sulfanilic acid azocromotrop (SAC) modified reduced graphene oxide (SAC-RGO) was prepared by simple non-covalent functionalization of graphene oxide (GO) followed by post reduction using hydrazine monohydrate. Spectral analysis (Fourier transform infrared, Raman and X-ray photoelectron spectroscopy) revealed that successful modification had occurred of GO with SAC through p-p interaction. The electrical conductivity of SAC-RGO was found to be similar to 551 S m(-1). The capacitive performance of SAC-RGO was recorded using a three electrode set up with 1 (M) aqueous H2SO4 as the electrolyte. The -SO3H functionalities of SAC contributed pseudocapacitance as evidenced from the redox peaks (at similar to 0.43 and 0.27 V) present in the cyclic voltammetric (CV) curves measured for SAC-RGO. The contribution of electrical double layer capacitance was evidenced from the near rectangular shaped CV curves and resulted in a high specific capacitance of 366 F g(-1) at a current density of 1.2 A g(-1) for SAC-RGO electrode. An asymmetric device (SAC-RGO//RGO) was designed with SAC-RGO as the positive electrode and RGO as the negative electrode. The device showed an energy density of similar to 25.8 W h kg(-1) at a power density of similar to 980 W kg(-1). The asymmetric device showed retention in specific capacitance of similar to 72% after 5000 charge-discharge cycles. The Nyquist data of the device was fitted with Z-view and different components (solution resistance, charge-transfer resistance and Warburg elements) were calculated from the fitted curves.
Keywords: ELECTROCHEMICAL PROPERTIES; CARBON NANOTUBES; PERFORMANCE; COMPOSITE; REDUCTION; GRAPHITE; SPECTROSCOPY; FABRICATION; HYDROGEL; NANOWIRE